Undergraduate Education Policy (UEP) 2023: A Framework to Promote Broad-based Education in Pakistan - Bashir, Arshad; Rehman, Ata-ur (The Lighthouse Journal of Social Sciences, 2023)
The Higher Education Commission (HEC) formulated the first-ever Undergraduate Education Policy (UEP) in 2020. After receiving feedback from relevant stakeholders, a revised policy (UEP-Version 1.1) has been notified by HEC for implementation with effect from fall 2023 in all universities/HEIs and affiliated colleges of Pakistan. This study explores the salient features of UEP with a special emphasis on the foundational constructs of the policy. The main objective of this study was to decipher the Liberal Arts model that has been used as a basis for formulating the UEP. A qualitative research method was used to explore the key concepts of the policy. The method included interviews with education consultants, officials of the Higher Education Departments of respective provinces, Vice Chancellors, Deans, Registrars, faculty, and students at mainstream universities located in major cities of Pakistan. Additionally, a focused group discussion was conducted to seek collective wisdom from academicians. The findings of the study revealed that the UEP would help the higher education sector to improve the quality of graduates produced from undergraduate programs through competence and broad-based education models. The findings of the study are useful for universities/HEIs and affiliated colleges in the process of implementing UEP effectively.